Therapeutic Modality of Mesenchymal Stem Cells for Moderate to Severe Knee Osteoarthtritis: A Systematic Review - Fathani, Irfan Jaen; Hanif Al Asad Budiyanto, Muhammad; Jannatin, Nurin ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Osteoarthritis (OA) is a chronic degenerative joint disease that commonly affects weight-bearing joints, such as the knee. A potential treatment is the intra-articular injection of mesenchymal stem cells (MSCs), which may stimulate joint tissue regeneration, cartilage formation, and angiogenesis. This systematic review aimed to evaluate the efficacy and safety of MSC therapy in moderate-to-severe knee OA.Methods: Literature searches were conducted using PubMed, Science Direct, Taylor and Francis, Google Scholar, Springer Link, Wiley, and the Garuda Portal. From the 644 identified articles, only seven randomized controlled trials published within the last 10 years met the inclusion criteria.Results: Five of the seven studies demonstrated significant reductions in pain based on Visual Analog Scale (VAS) scores following MSC injections. Four studies reported significant improvements in WOMAC scores, whereas one study showed no notable change. Adverse effects noted after injections included joint swelling, contusions, postprocedural hematomas, mild effusion, and injection site pain.Conclusions: Intra-articular MSC therapy shows potential for reducing pain and improving joint function in moderate-to-severe knee OA. Improvements in VAS and WOMAC scores suggest clinical benefits that can last up to 12–48 months post-treatment. MSC injections may be considered as a causal therapy in addition to symptomatic treatments, such as analgesics, to enhance patient quality of life.